Preliminary study of self-cleaning coating by applying nano titanium dioxide additive / Ng Pui Pui - Ng, Pui Pui (2015)

(untitled)
Environmental pollution has become a concern of the architectural industry as it causes aesthetical effects to urban buildings. Thus, the development of a coating which contains self-cleaning behavior plays a crucial role in the achievement of more competitive architectural coatings and to curb the cost of high maintenance. This preliminary study wish to test the effectiveness of Nano TiO2 as an additive prior more developments and formulations can be done. Due to the ability to accelerate degradation of many organic contaminants, nanometric titanium dioxide (TiO2) has been selected as the promising photocatalytic material. Nano TiO2 were pre-synthesized in dispersed form before it is incorporated into the acryllic based coating system, the existing formula of exterior paint Nippon Weatherbond colour bases i.e. Pastel Base and Deep Base. The nanometric size of nano TiO2 were experimentally examined by using SEM and the optimal dosage of the nano TiO2 in the coating will be determined from the experiments. Physical properties such as opacity, whiteness and colour were determined by using the right tools. A series of coating properties tests e.g. application test, harsh weather resistance test, UV irradiation resistance, dirt pick-up test and etc were carried out to study the properties of self-cleaning coating in terms of wet paint and dry paint film. Paint film surface morphology such as hydrophilicity and contact angle were being studied as well. The results shown that coatings with NanoTiO2 additive with 3% dosage is able to perform better in terms of self-cleaning, which can be significantly observed through Dirt Pick Up Resistance Test, Dirt Streak Mark Test, photocatalytic effectiveness, contact angle measurement and etc.